Variability analysis of a sample of potential southern calibration sources - Hungwe, Faith (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2009)
A considerable number of Very Long Baseline Interferometry (VLBI) surveys have been conducted in the northern hemisphere and very few in the southern hemisphere mostly because of a lack of telescopes and therefore adequate baseline coverage. Thus there is a deficit of calibrator sources in the southern hemisphere. Further, some of the most interesting astronomical objects eg. the galactic centre and the nearest galaxies (the small and large Magellanic Clouds) lie in the southern hemisphere and these require high resolution studies. With a major expansion of radio astronomy observing capability on its way in the southern hemisphere (with the two SKA (Square Kilometre Array) precursors, meerKAT (Karoo Array Telescope) and ASKAP (Australian SKA Pathfinder), leading to the SKA itself) it is clear that interferometry and VLBI in the southern hemisphere need a dense network of calibration sources at different resolutions and a range of frequencies. This work seeks to help redress this problem by presenting an analysis of 31 southern sources to help fill the gaps in the southern hemisphere calibrator distribution. We have developed a multi-parameter method of classifying these sources as calibrators. From our sample of 31 sources, we have 2 class A sources (Excellent calibrators), 16 class B sources (Good calibrators), 9 class C sources (Poor calibrators) and 4 class D sources (Unsuitable calibrators).
Keywords: Southern sky (Astronomy); Radio sources (Astronomy); Active galactic nuclei; Very Long Baseline Array (Telescopes); Calibration Radio telescopes -- Southern Hemisphere; Radio astronomy -- Southern Hemisphere; Radio interferometers; Very long baseline interferometry; Radio astronomy -- Observations; Radio astronomy -- South Africa; Radio telescopes -- South Africa; Square Kilometer Array (Spacecraft)